Investigating the prevalence of febrile convulsion in Kayseri, Turkey: An assessment of the risk factors for recurrence of febrile convulsion and for development of epilepsy. (February 2018) - Canpolat, Mehmet; Per, Huseyin; Gumus, Hakan; Elmali, Ferhan; Kumandas, Sefer
Highlights: The prevalence of febrile convulsion (FC) in Kayseri is 43/1000. The risk of recurrence of FC increases 7.1-fold in individuals with a history of FC in first and second degree relatives. The risk of recurrence increases 17.6-fold in subjects with pre-FC fever <39 °C. Risk of recurrence increases 17.8-fold in subjects with pre-FC duration of fever <1 h. Risk of epilepsy increases 21.1-fold in subjects with FC convulsion and neurodevelopmental abnormality. Abstract: Purpose: The purpose of this study was to investigate the prevalence and recurrence of febrile convulsion (FC) and risk factors for development of epilepsy in school children throughout in the Kayseri provincial center. Method: Ten thousand individuals selected using "stratified cluster sampling" from a student population of 259, 428 inside the Kayseri Urban Municipality represented the study sample. Fifteen thousand questionnaires were distributed, of which 10, 742 (71.6%) were returned. Telephone interviews were performed with the families of the students reported as having undergone FC, and the medical records of patients with a history of hospitalization were evaluated. Data were analyzed on IBM SPSS Statistics 22.0 package program. Significance was set at p  < 0.05. Results: Prevalence of FC was 4.2% in girls and 4.3% in boys, with a total prevalence of 4.3%. Recurrence of FC was observed in 25.4% of cases. Risk of recurrence increased 7.1 times in subjects with a history of FC in first and second degree relatives, 17.8 times in those with fever interval <1 h before convulsion and 17.6 times in those with pre-convulsion body temperature <39 °C. Epilepsy developed in 33 (7.2%) cases. Neurodevelopmental abnormality was the most important risk factor for epilepsy (21.1-fold risk increase). Conclusions: Analysis revealed that FC with a good prognosis had a high rate of recurrence and a higher risk of epilepsy than in the general population. The prevalence of FC in the province of Kayseri was closer to that in developed rather than developing countries.